An Aristocratic Compatibilist's Providence : Components of Aquinas's Soft Determinist View - Dvorský, Petr, (Early Modern History and Modern History E-Books Online, Collection 2024., 2024)
This monograph discusses different philosophical and theological components of Aquinas's view regarding the relation between human agency and divine providence. Against many contemporary scholars it argues that this view includes a plausible for